Arguing from identity: ontology to advocacy in Charles Taylor's political thought - Sadian, Samuel Dominic (Rhodes University, Faculty of Humanities, Department of Political and International Studies, 2009)
In this thesis I discuss three normative claims that I take to be central elements of Charles Taylor's political thought. The first of these is Taylor's contention that, in contemporary pluralistic societies, justifying socially prevailing norms by appealing to universally binding moral values is unlikely to promote social solidarity. Because this approach tends to downplay the goods that people realise through membership in particular associations, Taylor believes we must adopt a model of justification that does not prioritise universal over particular goods if we are to further social co-operation. A second claim Taylor defends is that commitment to the liberal value of collective self-rule implies treating patriotically motivated public service as a non-instrumental good. We should not, Taylor argues, regard collective association as nothing more than a means to satisfying private goals. Taylor advances a third claim, that is, he maintains that liberal toleration for diverse ways of life may require a perfectionist state that supports particularistic ways of life when they are threatened by decline. I offer a qualified defence of the first two claims, but suggest that the third is less compelling. I attempt to do this by evaluating Taylor's claims against the standards of lucid argumentation that he himself lays down. In discussing social and political norms, which he describes as "advocacy" issues, Taylor argues that our normative commitments necessarily rely on an underlying social ontology. More specifically, Taylor argues that the political values we defend are those that enable us to secure the interests we have as the bearers of an identity possessing both individual and collective dimensions. In setting out the conditions that favour integrated and free identity formation we may thereby reach a clearer understanding of the political norms that we wish to endorse. I argue that, while Taylor's ontological reflections might well incline us to accept his model of justification and his account of patriotic social commitment, they do not of themselves dispose us to accept state perfectionism.
Keywords: Taylor, Charles, 1931- -- Political and social views; Taylor, Charles, 1931- -- Criticism and interpretation; Cultural pluralism; Political culture; Identity (Philosophical concept); Ontology